Cruise tourism in the context of COVID-19: Dilemmas and solutions (2022)
COVID-19 cases on international cruise ships have attracted extensive attention from the international community as well as the world’s tourism and shipping industry. This virus highlighted the plight that must be faced by cruise ships in complicated times and situations such as pandemics. The comparative method is adopted to analyze the management measures taken by the “Diamond Princess”, “Costa Serena”, “Westerdam” and “Grand Princess” cruises in response to the COVID-19 pandemic and then to summarize the common dilemmas faced by these cruise ships, including defects of their internal environment, unclear health-care obligations during an epidemic, weak collaboration between the parties involved and their limited performance, and widespread infodemic and unfavorable public opinion. Given these dilemmas, measures are suggested to deal with the “cruise dilemma”, including establishing and defining isolation standards on boards, enhancing the capacity of international organizations, the international community’s joint response to the pandemic, promoting cooperation between countries, building an effective mechanism for the broad participation of the whole society, and standardizing the release of information and reasonably guiding public social opinion.